Pengembangan hermeneutika hukum al-Shāṭibī dalam konteks tafsir tematik al-Qur'an: Analisis kritis terhadap karya Mohamed El-Tahir El-Mesawi - Maulidiyah, Izatul Muhidah; Mubarok, Achmad Sofiyul (AL-MUQARANAH, 2025)
This study explores the development of al-Shāṭibī’s legal hermeneutics in the context of thematic Qur’anic exegesis, with a critical analysis of Mohamed El-Tahir El-Mesawi’s works. The main focus is to identify both the contributions and limitations of El-Mesawi’s thought, which emphasizes the epistemological dimension of maqāṣid al-sharīʿah but has yet to provide an operational methodological framework for thematic exegesis. This research employs a qualitative library-based method with critical hermeneutical analysis and a maqāṣidī approach. The findings reveal that El-Mesawi’s framework remains normative and conceptual, thereby requiring the development of a more practical model. This article proposes a five-step operational methodology for maqāṣid-based thematic exegesis: theme identification, verse compilation, semantic-contextual analysis, social verification, and the formulation of sharīʿah-oriented solutions. This model highlights the importance of integrating Qur’anic texts, maqāṣid al-sharīʿah, and contemporary social realities so that exegesis transcends normative discourse and becomes a responsive tool for addressing modern challenges. Theoretically, this study enriches Qur’anic hermeneutics by expanding the horizon of maqāṣidī exegesis toward a more applicable framework. Practically, the proposed model provides guidance for academics, exegetes, and Islamic educational institutions in producing contextual interpretations that respond to urgent issues such as social justice, gender equity, and environmental sustainability.